Performance and Emission Characteristics of a Diesel Engine Fuelled with Biodiesel extracted from Linseed oil - Bhatti, Umesh (My University, 2013)
The depleting reserves of petroleum and environmental issues have led to the search for more environmental-friendly and renewable fuels. Biodiesel obtained from various renewable sources has been recognized as one of the alternative fuel due to its biodegradability, high cetane no, no sulphur emissions and low volatility. Biodiesel derived from non edible feed stocks such as linseed oil are reported to be feasible choices for developing countries including India where consumption and cost of edible oil is very high .The aim of present work is to optimize the biodiesel production from linseed oil through tranesterification process. The optimum conditions for maximum yield were obtained at molar ratio of 5:1, reaction time 60 minutes, and at 0.5% catalyst concentration. The various performance and emission parameters like brake mean effective pressure (BMEP), brake power (BP), brake specific fuel consumption(BSFC), mechanical efficiency (Mech. Eff.), brake thermal efficiency (BthEff), CO emissions, CO2 emissions, HC emissions, NOx emissions were evaluated at different loads and compression ratios in a 4 stroke, single cylinder variable compression ratio engine. These performance and emission parameters of diesel fuel were compared with that of B10, B15, and B20. The performance parameters of B10 blend were similar to those of diesel. It was found that CO2, HC and CO emissions decreases as the blend content increases whereas the NOx emissions increases as the blend content increases
ME, MED
Keywords: Biodiesel, transesterification, free fatty acid, molar ratio, compression ratio